The MILAN Campaign: Studying Diel Light Effects on the Air–Sea Interface - Stolle, Christian (2019)
The sea-surface microlayer (SML) at the air-sea interface is < 1 mm deep but it is physically, chemically and biologically distinct from the underlying water and the atmosphere above. Wind-driven turbulence and solar radiation are important drivers of SML physical and biogeochemical properties. Given that the SML is involved in all ocean-atmosphere exchanges of mass and energy, its response to solar radiation, especially in relation to how it regulates the air-sea exchange of climate-relevant gases and aerosols, is surprisingly poorly characterised. MILAN (sea-surface MIcroLAyer at Night) was an international, multidisciplinary campaign designed to specifically address this issue. In spring 2017, we deployed diverse sampling platforms (research vessels, radio-controlled catamaran, free-drifting buoy) to study full diel cycles in the coastal North Sea SML and in underlying water, and installed a land based aerosol sampler. We also carried out concurrent ex situ experiments using several microsensors, a laboratory gas exchange tank, a solar simulator, and a sea spray simulation chamber. In this paper we outline the diversity of approaches employed and some initial results obtained during MILAN. Our observations of diel SML variability, e.g. the influence of changing solar radiation on the quantity and quality of organic material, and diel changes in wind intensity primarily forcing air-sea CO2 exchange, underline the value and the need of multidisciplinary campaigns for integrating SML complexity into the context of air-sea interaction